Simultaneous fluoroscopic and nuclear imaging: impact of collimator choice on nuclear image quality. Issue 1 (3rd January 2017) - van der Velden, Sandra; Beijst, Casper; Viergever, Max A.; de Jong, Hugo W. A. M.
Abstract : Purpose: X‐ray‐guided oncological interventions could benefit from the availability of simultaneously acquired nuclear images during the procedure. To this end, a real‐time, hybrid fluoroscopic and nuclear imaging device, consisting of an X‐ray c‐arm combined with gamma imaging capability, is currently being developed (Beijst C, Elschot M, Viergever MA, de Jong HW. Radiol . 2015;278:232–238). The setup comprises four gamma cameras placed adjacent to the X‐ray tube. The four camera views are used to reconstruct an intermediate three‐dimensional image, which is subsequently converted to a virtual nuclear projection image that overlaps with the X‐ray image. The purpose of the present simulation study is to evaluate the impact of gamma camera collimator choice (parallel hole versus pinhole) on the quality of the virtual nuclear image. Methods: Simulation studies were performed with a digital image quality phantom including realistic noise and resolution effects, with a dynamic frame acquisition time of 1 s and a total activity of 150 MBq. Projections were simulated for 3, 5, and 7 mm pinholes and for three parallel hole collimators (low‐energy all‐purpose (LEAP), low‐energy high‐resolution (LEHR) and low‐energy ultra‐high‐resolution (LEUHR)). Intermediate reconstruction was performed with maximum likelihood expectation‐maximization (MLEM) with point spread function (PSF) modeling. In the virtual projection derived therefrom, contrast, noise level, and detectability were determined and compared with the ideal projection, that is, as if a gamma camera were located at the position of the X‐ray detector. Furthermore, image deformations and spatial resolution were quantified. Additionally, simultaneous fluoroscopic and nuclear images of a sphere phantom were acquired with a physical prototype system and compared with the simulations. Results: For small hot spots, contrast is comparable for all simulated collimators. Noise levels are, however, 3 to 8 times higher in pinhole geometries than in parallel hole geometries. This results in higher contrast‐to‐noise ratios for parallel hole geometries. Smaller spheres can thus be detected with parallel hole collimators than with pinhole collimators (17 mm vs 28 mm). Pinhole geometries show larger image deformations than parallel hole geometries. Spatial resolution varied between 1.25 cm for the 3 mm pinhole and 4 cm for the LEAP collimator. The simulation method was successfully validated by the experiments with the physical prototype. Conclusion: A real‐time hybrid fluoroscopic and nuclear imaging device is currently being developed. Image quality of nuclear images obtained with different collimators was compared in terms of contrast, noise, and detectability. Parallel hole collimators showed lower noise and better detectability than pinhole collimators.